PENINGKATAN SOLIDARITAS SOSIAL MELALUI PROGRAM BERBAGI TAKJIL DI KELURAHAN BEDURI, KECAMATAN PONOROGO, KABUPATEN PONOROGO TAHUN 2024 - Huda, Fatakhul; Siti Khusnul Faizah (Institut Agama Islam Riyadlotul Mujahidin, 2025)
Abstract Social solidarity is the main pillar in creating a harmonious and inclusive society. In the midst of increasing modernization and individualism, the tradition of sharing takjil in Beduri Village, Ponorogo District, Ponorogo Regency, is one of the important efforts to strengthen social solidarity. The program involves various elements of the community, ranging from religious leaders to youth, who come together to help those who are less fortunate, especially before breaking the fast. Apart from being an act of worship, this activity also serves to strengthen social relations between residents, foster the value of togetherness, and increase a sense of concern for others. This study aims to analyze the impact of the takjil sharing program on the social solidarity of the local community, using a descriptive qualitative approach. The results show that the takjil sharing program in Beduri Village not only strengthens social relations, but also has a positive impact on the local economy, especially for small businesses that provide raw materials for takjil. The program also strengthens the community's religious awareness of the importance of helping each other, and strengthens the bond between individuals through the religious values taught during Ramadan. However, challenges related to reliance on donations that are not always consistent and unstructured management need to be overcome for the program to be sustainable. This research recommends the importance of more organized management and involving more parties, including the private sector and other institutions, to support the sustainability of the program. The findings are expected to contribute to the development of similar programs in other regions, as well as enrich the study of social solidarity in the local context of Indonesia.